2015
DOI: 10.1124/jpet.115.229005
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Insulin Resistance by Mangiferin in a Rat Model of Fructose-Induced Metabolic Syndrome Is Associated with Modulation of CD36 Redistribution in the Skeletal Muscle

Abstract: Mangiferin is one of the prominent active components responsible for the antidiabetic property of many traditional herbs, but its underlying mechanisms of action remain unclear. CD36 in skeletal muscle is known to contribute to the etiology of insulin resistance by facilitating fatty acid uptake. This study investigated the effect of mangiferin on insulin resistance. The results showed that treatment of Wistar-Kyoto rats with mangiferin (15 mg/kg, once daily, by oral gavage) for 7 weeks inhibited chronic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…Triglyceride content in red gastrocnemius was determined as described previously . Briefly, suitable aliquots of tissue homogenates were extracted and were analyzed for their triglyceride content with an enzymatic assay kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triglyceride content in red gastrocnemius was determined as described previously . Briefly, suitable aliquots of tissue homogenates were extracted and were analyzed for their triglyceride content with an enzymatic assay kit.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described previously . Total protein was prepared from the red gastrocnemius, liver, and eWAT using the kit for tissue protein extraction (Thermo Fisher Scientific, Sunnyvale, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…FFAs can be uptaken by several tissues via FFA transport proteins (FATPs) and CD36, both highly expressed in heart, adipose tissue, and skeletal muscle [69]. Fructose upregulates CD36 expression in adipose tissue [70] and skeletal muscle [71] to facilitate FFA uptake, resulting in local insulin resistance. Increased FFAs promote autophagy in skeletal muscle of mice with high fructose diet, likely as a compensate mechanism for clearance of lipotoxic intermediates [30].…”
Section: Direct Dangerous Factors Under High Fructose Consumptionmentioning
confidence: 99%
“…Recently, it has been reported that MGF can attenuate high-fat diet (HFD)-induced metabolism syndrome through activating AMP-actived protein Kinase (AMPK) for abnormal lipid metabolism regulation, anti-inflammation, and insulin resistance improvement [19]. A recent study demonstrates that MGF can ameliorate endothelial dysfunction by regulating AMPK to inhibit the inflammation in ER stress [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mangiferin (MGF) is one of the main constituents in common anemarrhena, a traditional medicine, for treating diabetes [19][20][21]. Recently, it has been reported that MGF can attenuate high-fat diet (HFD)-induced metabolism syndrome through activating AMP-actived protein Kinase (AMPK) for abnormal lipid metabolism regulation, anti-inflammation, and insulin resistance improvement [19].…”
Section: Introductionmentioning
confidence: 99%